« L’Autre » juif américain : l’emprunt lexical au yiddish dans l’anglais américain des films de Woody Allen, un enjeu pour le doublage - Frédérique Brisset (Lexis: Journal in English Lexicology)
Woody Allen is considered the heir to the greatest American burlesque artists, first of all the Marx Brothers, for he embodies a Jewish humor tradition, as they also do. His Jewishness is more cultural than religious, as can be seen in the self-derision applied to his own alter egos, clear references to the traditional Schlemiel character. It also implies the repeated borrowing of Yiddish words.Those loan words are largely assimilated by American speakers, since the linguistic contribution from Yiddish to American English and its influence widely outgrows the Jewish American circle. This impact can be ascribed to a massive Jewish presence in the media and entertainment industries, and to the easy transfer process from Yiddish to American English due to their common German origin. But far beyond the usual technical or cultural reasons for borrowing, Yiddishisms often have an affective aim in speech, due to specific lexical shifts which occur while these loan words are integrating the American language. This and the cultural connotations they bear imply special difficulties when translated into a third language, as can be seen in the French dubbed versions of Allen’s films.